PENGARUH PEMBERIAN JAMINAN SOSIAL TENAGA KERJA DAN INSENTIF TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PT. EKA DURA INDONESIA (PALM OIL MILL) ROKAN HULU - Helma Nopri Yosa; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at PT.Eka Dura Indonesia (PALM OIL MILL) Rokan Hulu located in Kunto Darussalam District of Rokan Hulu Regency. The problem in this research is not achievement targets realization of production company in last 5 years and percentage of target achievement fluctuates and tends ti decline in 2016. This is allegedly influenced by the employees performance on the company. This study aims to determine the influence of Sosial Security and Incentive on the performance of employees of PT.Eka Dura Indonesia (PALM OIL MILL) Rokan Hulu.In this research the method used is descriptive quantitative with SPSS program version 17. The population in this research is all employees of production part of PT.Eka Dura Indonesia (PALM OIL MILL) Rokan Hulu which amounted to 171 employees. Samples taken based on method using slovin formula is 63 respondents. Methods of data collection using questionnaires. And calculation of coefficient of determination (R2) simple provision of social security for employee performance is obtained value equal to 0,556 or 55,6% and Incentive for employee performance is obtained value equal to 0,454 or 45,4% Hypothesis testing using multiple linear analysis method with result of research that is Y= .The research that has been done show the result that the respondent's response to Social Security, Incentive and employee performance in PT. Eka Dura Indonesia (Palm Oil Mill) in good category. While for the T test that has been done shows that the variable of Social Security and Incentive partially significant effect on employee performance. And F test results show that simultaneously Social Security and Incentive significant effect on employee performance in PT. Eka Dura Indonesia (Palm Oil Mill) Rokan Hulu. And for calculation of coefficient of determination (R2) obtained value of R Square equal to 0,590. This shows that Social Security and Incentive give effect of 59%, while the rest 41% influenced by other variable not examined in this research.Keywords : Social Security, Incentive, Employee Performance